REPRESENTASI GENDER DALAM RETORIKA POLITIK ISLAM MASA KEMERDEKAAN - Retno Endah Wardani; Adzrah Dwi Sunarty Abas; Sidqi Ali; Miftahul Huda (JUSAN: Jurnal Sejarah Peradaban Islam Indonesia, 2026)
This study examines gender representation in Islamic political rhetoric during Indonesia’s independence period, focusing on how women were portrayed in Islamic and nationalist discourses. The study aims to analyze the construction of women’s roles in Islamic political rhetoric during the 1940s and early 1950s, a period marked by the formation of Indonesia’s national identity and political system. This research employs a qualitative approach using library research. Data were collected from secondary sources, including scholarly journal articles, books, previous studies, and other academic publications related to Islamic politics, gender, and socio-political dynamics during the independence era. The data were analyzed through content analysis involving data reduction, thematic categorization, interpretation, and conclusion drawing. The findings indicate that women were represented in three dominant forms: as moral symbols of society, supporters of the national struggle, and guardians of the domestic sphere. These representations acknowledged women’s contributions to society and nation-building while simultaneously positioning them within family-oriented and moral responsibilities. The study concludes that Islamic political rhetoric during the independence period played an important role in shaping gender norms and public perceptions of women’s roles, while also reinforcing limitations on women’s participation in formal political spaces.